Acrocyanosis - An uncommon event at post anaesthesia recovery room- A case report - Hossain, Md Azmal; Begum, Mosammat Maksuhuda (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
A healthy patient of aged 26 years underwent left ureter-lithotomy and cystostomy under general anesthesia. In post-operative ward, both extremities were cold & nailed were cyanosed. This cyanosis persisted for as long as 8-10 hours. No abnormality was detected in arterial blood gas analysis. This is not a simple peripheral cyanosis induced by cold environment of operation theatre, as warming usually reverses the phenomenon within a short period. But in this case, peripheral cyanosis persisted for as long as 8-10 hours. Therefore, this is a case of acrocyanosis. DOI: http://dx.doi.org/10.3329/jbsa.v26i1.19819 Journal of Bangladesh Society of Anaesthesiologists 2013; 26(1): 58-60